2018
DOI: 10.1002/prep.201800039
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystallisation of Ammonium DiNitramide (ADN) by Spray Flash Evaporation (SFE)

Abstract: Ammonium DiNitramide (ADN) is an interesting oxidizer to replace ammonium perchlorate in the composition of solid propellants. In this study, Spray Flash Evaporation (SFE) is presented as a new technology to enhance stability of ADN by crystallization of nanoparticles. The crystallinity and purity of the compound was confirmed by X‐Ray Diffraction and Raman analysis. An average diameter of spherical particles around 32 nm (solution of ethyl acetate) and 34 nm (solution of methyl acetate) was measured by Scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Complementary experiments, which were achieved with ADN packed at 60 % of its TMD, showed that the shockwave released by the detonator activates the detonation of powdered ADN, leading to effects stronger than those produced by ADN pressed at 99 % of its TMD, but weaker than those resulting from the detonation of liquid ADN ( Table 1). The formation and the propagation of a detonation wave in an ADN nanopowder with a low density, of only 16 % of ADN theoretical maximal density, have been recently reported by Berthe et al [13]. In this experiment, the detonation front propagates through an ADN charge with a diameter of only 3 mm, at a steady velocity of 1920 m/s.…”
Section: Detonation Tests With Adnsupporting
confidence: 69%
See 1 more Smart Citation
“…Complementary experiments, which were achieved with ADN packed at 60 % of its TMD, showed that the shockwave released by the detonator activates the detonation of powdered ADN, leading to effects stronger than those produced by ADN pressed at 99 % of its TMD, but weaker than those resulting from the detonation of liquid ADN ( Table 1). The formation and the propagation of a detonation wave in an ADN nanopowder with a low density, of only 16 % of ADN theoretical maximal density, have been recently reported by Berthe et al [13]. In this experiment, the detonation front propagates through an ADN charge with a diameter of only 3 mm, at a steady velocity of 1920 m/s.…”
Section: Detonation Tests With Adnsupporting
confidence: 69%
“…The formation and the propagation of a detonation wave in an ADN nanopowder with a low density, of only 16 % of ADN theoretical maximal density, have been recently reported by Berthe et al . . In this experiment, the detonation front propagates through an ADN charge with a diameter of only 3 mm, at a steady velocity of 1920 m/s.…”
Section: Resultsmentioning
confidence: 91%
“…Crystallization of ADN was successfully performed by Berthe et al . for a nozzle pressure of 2 MPa and a nozzle temperature of 110 °C in ethyl or methyl acetate [35]. Spherical particles of ADN were produced with mean size of 37 nm+/−5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The size reduction is performed by recrystallization on the submicron scale using the Spray Flash Evaporation process. This technology proved its ability to produce submicron explosives and oxidants [34,35] as well as non-energetic organic compounds, co-crystals and diverse composites [36,37]. It is based on the spray of a superheated solution.…”
Section: Introductionmentioning
confidence: 99%
“…Green propellants have become a research hotspot in recent years, ammonium dinitramide (ADN) is energy, nontoxic and pollution-free new energetic material, which has been used in missiles, rockets and thrusters [24][25][26][27][28]. ADN based energetic ionic liquid propellants are expected to be used as replacements for hydrazine and also for ionic liquid gel propellants [29].…”
Section: Introductionmentioning
confidence: 99%